Heat Dissipation Enhancement Using Staggered Fin Heat Sink - Ong, Zi Hui (Universiti Sains Malaysia, 2022)
The current study focuses on the computational evaluation of the heat dissipation of staggered plate fin heat sinks (PFHS). The simulation setup consists of an aluminium alloy 6061 heat sink exposed to impinging air flow with Reynolds number in the range of 1333 to 5334 at 25 ℃. A constant heat flux of 18750 WM-2 is applied at the bottom surface of the heat sink. A parametric study is carried out to study the influences of the geometric and flow parameters on the heat sink performance. The results show that the staggered PFHS shows a lower thermal resistance and higher pumping power required as compared with the conventional PFHS. Among the inclination angles studied involving θ = 0˚, 30˚, 60˚, 90˚, alternating 30˚, and alternating 60˚, the staggered PFHS with θ = 90˚ shows the highest increase in both Nusselt number and pumping power required in comparison to the conventional PFHS, whereas configuration with θ = 0˚ yields the best trade-off between Nusselt number and pumping power required. Alternating the θ = 30˚ and θ = 60˚ configurations result in better heat dissipation performance of the heat sink in comparison to that without alternation, albeit with an increase in the pumping power required. As As SL/L increases from 0.81 to 1, the thermal resistance of the heat sink decreases slightly while the pumping power of the heat sink increases. The longitudinal fin pitch of the heat sink has no significant effect on its trade-off between Nusselt number and pumping power required. As compared with the staggered PFHS with wall, the no wall configuration exhibits a slightly lower thermal resistance but a lower average Nusselt number. The no wall configuration shows a lower pumping power required, as well as a better trade-off performance between Nusselt number and pumping power.